The ILCA/ILRAD trypanotolerance network. Situation report, December 1985 - International Livestock Centre for Africa (1986)
Report of an internal meeting by researchers from thirteen sites in the ILCA Trypanotolerance Research Network. Presents and discusses the origins of the network; the network in December 1985 (objectives, sites & organisation); protocols, training and support services; preliminary indications from individual sites; a review of some current findings relevant to network operations; and a major analysis and network research in 1986.